Framing ecological issues in local political contestations as part of political communication in the 2018 regional election - Yustisia, Ika Rizki; Purnomo, Joko; Maksum, Ali (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2023)
This paper discusses the practice of political communication carried out by regional head candidates in the City of Kediri in the 2018 local elections in East Java. This paper focuses on conducting in-depth tracking of the framing of ecological issues in campaign practices carried out by regional head candidates in the 2018 local elections. This study aims to gain an understanding and knowledge related to the political communication practices of regional head candidates in responding to ecological issues in political contestation locally in East Java. This research uses a descriptive qualitative approach that focuses on collecting data through interviews and documentation related to the political communication strategies of the 2018 Kediri mayoral candidates in communicating ecological issues to the public. The study results show that the political communication practices carried out by candidates in the 2018 regional elections have yet to make ecological issues a critical public issue. This is reflected in the campaign's content, which still focuses on socio-economic issues that prioritize aspects of infrastructure development for the community, not directing environmental conservation practices to support sustainable development.